LACK AND DESIRE IN WALKER’S NOVEL THE COLOR PURPLE: A POSTMODERN STUDY - Ijaz, Rabia (University of Wah Journal of Social Sciences, 2023)
This paper explores the dimensions of lack and desire in the characters of the Color Purple. The dimensions are individual or psychological and historical lack. The result mentions that there are multiple reasons for the Lack that one can see in the characters of the novel. In the context of structuralism, Lacan made some significant contributions to defining the unconscious and formulating the concept of desire. Lacan describes desire as a state of loss when discussing the complexity of desire. The research findings that how the idea of lack is linked to the idea of desire and the idea of desire is related to lack. Firstly, individual or psychological lack could be seen through the actions and behavior of the characters. Celie, the protagonist in the novel, went through physical or psychological violence firstly by her father and then by her husband. Her lack can be seen when she internalizes everything that happened to her and thinks she is worthless. >>>>>>>>>Acts in a way that betrays a lack of understanding, kindness, and respect for other people, especially the ladies in his life. He is shown as being bossy and manipulative towards his wife and as being physically and sexually abusive towards his daughter Celie throughout the entire novel. Secondly, historical lack led to the character in the novel. This research has discovered Walker’s novel from the Lacan point of view. It starts with the fall of the characters and then their growth. In this research, all the dimensions and reasons have been discussed clearly. This research has discovered Walker’s novel from the Lacan point of view. It starts with the fall of the characters and then their growth. In this research, all the dimensions and reasons have been discussed clearly. Key words: African American history, rape, racial discrimination, Lacan, lack, incest and desire, and subject, self- realization.